Role of abscisic acid in legumes under abiotic stress - Llanes, Analia Susana (2014)
Abscisic acid (ABA) is a phytohormone that regulates several developmental processes and adaptive stress responses in plants. Legumes are a group of plants that are highly important food, feed and biofuel crops. Adaptation of these plants is a key factor that could determine the future impact of climatic change on agriculture. Many roles for ABA in legume plants have been identified, but their importance under abiotic stress remains unclear. Recently, numerous advances have led to the identification of these ABA roles, and to a better understanding of how growth responses are controlled by ABA under abiotic stress. Different strategies are being employed to improve plant growth under abiotic conditions; one of them is the production of tolerant legume genotypes. Many attempts to enhance the tolerance to abiotic conditions have been made, including exogenous application of ABA hormone. This chapter presents a review of what is currently known about the role of ABA in legume plants under abiotic conditions.